2009
DOI: 10.1007/s10823-009-9095-9
|View full text |Cite
|
Sign up to set email alerts
|

Vignette Methodology and Culture-Relevance: Lessons Learned through a Project on Successful Aging with Iranian Immigrants to Sweden

Abstract: It is a well-known fact that cultural values play an important role in the construction of aging and old-age related understandings. This is why ethnogerontologists have tried to expand the gerontological imagination by arguing that research needs to become more culturally-relevant. Tapping into the values that people uphold and the understandings of aging that are shaped by them is a challenging endeavor. This is especially the case if one does not share the cultural background of the people whose values one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 62 publications
2
61
0
5
Order By: Relevance
“…Other results from this project can be found in Hammarströ m and Torres ( , 2009) as well as in Torres and Hammarströ m (2005. 4.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Other results from this project can be found in Hammarströ m and Torres ( , 2009) as well as in Torres and Hammarströ m (2005. 4.…”
Section: Discussionsupporting
confidence: 53%
“…Torres (2001Torres ( , 2003Torres ( , 2009) used vignette methodology to clarify the relationship between cultural values and understandings of successful aging, and found that there are a variety of ways in which this construct can be understood. Her findings show that not everybody associates aging well with the mastering of nature and with the future and productivity orientation that is so common in established definitions of successful aging within mainstream gerontology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The sequence of the four vignettes was randomly chosen and varied from respondent to respondent. Vignettes are short hypothetical scenarios designed to elicit people's perceptions, beliefs and attitudes (Torres 2009). By using vignettes, we were able to reveal the options lonely and non-lonely older adults consider for coping with loneliness.…”
Section: Copingmentioning
confidence: 99%
“…Content-specific vignettes depicting 5 relevant situations (Veal, 2002) can be useful for exploring sensitive topics which participants may be reluctant to discuss. This approach allows participants to retain some distance from the situations described, and is thought to be experienced as less threatening than direct inquiry (Barter & Renold, 1999;Torres, 2009). The responses that participants give offer an insight into their understanding of the situation and the representations and beliefs that underlie their understanding (Torres, 2009;VonDras, 2009).…”
mentioning
confidence: 99%
“…This approach allows participants to retain some distance from the situations described, and is thought to be experienced as less threatening than direct inquiry (Barter & Renold, 1999;Torres, 2009). The responses that participants give offer an insight into their understanding of the situation and the representations and beliefs that underlie their understanding (Torres, 2009;VonDras, 2009). There is no requirement to relate the information to the self, although selfreferences may be made spontaneously.…”
mentioning
confidence: 99%